Pengaruh Keteladanan Pimpinan dan Kompensasi terhadap Disiplin Kerja(Studi Kasus: Perusahaan Alat Kesehatan) - Erifebriani, Erifebriani (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Leadership Exemplars, Compensation and Work Discipline. This study aims to see how the influence of leadership exemplars on work discipline, the influence of compensation on work discipline, and the influence of leadership exemplars and compensation simultaneously on employee work discipline at PT. Bina Artha Semesta. Data collection techniques using questionnaires and interviews. Data analysis using SPSS (Statistical Package for the Social Science) with descriptive and quantitative methods, namely analysis that is the sum of the values ​​of the data obtained which are tabulated using multiple regression formulas. Based on the results of the study, the R value is 0.869, which indicates a positive linear relationship between leadership exemplars and compensation simultaneously influencing employee work discipline at PT. Bina Artha Semesta by 75.6%. While the remaining 24.4% is influenced by other factors not discussed in this study. From the test, it is known that the regression calculation obtained an F value of 46.478 with a significance level of 0.000 with (α) 5%. This shows that together, the variables of exemplary leadership and compensation have a significant effect on employee work discipline